Towards Educational Excellence: Utilizing Education Hotels as an Innovative Learning Base for Hospitality Accommodation Program Students - Andriani, Shella; Ramanayaka, Lathisha; Bhatt, Vaibhav (Journal Evaluation in Education (JEE), 2024)
Purpose of the study: The aim of this research is to evaluate the effectiveness of using the Education Hotel as a base for innovative learning for students of the hotel accommodation program at public vocational secondary schools 4 Jambi City. Methodology: The type of research used in this research is naturalistic qualitative. The sample for this research was 30 students of the hospitality accommodation skills program at public vocational secondary schools 4 Jambi City. The data collection technique used is observation. The data analysis technique in this research will be carried out holistically and structured, in accordance with a naturalistic qualitative approach. Main Findings: The use of Edotel at public vocational secondary schools 4 Yogyakarta by students of the hotel accommodation program based on the Front Office sector is included in the high category. Meanwhile, the use of Edotel at public vocational secondary schools 4 Jambi City by students of the hotel accommodation program based on Housekeeping is in the low category.. Novelty/Originality of this study: This research presents a new concept by introducing an innovative approach using Hotel Education as the main learning platform for Hospitality Accommodation Program students.